PENGARUH PROFITABILITAS, KEBIJAKAN HUTANG DAN DIVIDEND PAYOUT RATIO (DPR) TERHADAP NILAI PERUSAHAAN - oktavia, Oky; Desmintari, Desmintari (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2016)
This study aimed to examine the effect of Profability, Policy Liabilities and Dividend Payout Ratio (DPR) of Company Value basic industry and chemical companies listed in Indonesia Stock Exchange period 2011 to 2014. The population in this study a number of 63 companies listed in Indonesia Stock Exchange. Data obtained from financial statements 2011 to 2014 that has been published. Obtained a total sample of 11 companies. The analysis technique used is multiple linear regression and hypothesis testing with constant 5%. The results showed that significantly effect profitability, policy liabilities does not have a significant effect and dividend payout ratio (DPR) does not have a significant effect. The coefficient of determination R square indicates 0.326 or 32.6% of explaining that the variable is explained by the variable company value and profitability, policy liability and dividend payout ratio (DPR) the remaining 67.4% is explained by other variables.